1982
DOI: 10.1007/bf01965116
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic asthma and bacterial histamine release

Abstract: In this study of intrinsic asthma (IA) in children the pathogenic role of bacteria in respiratory disease was elucidated by a basophil histamine liberation technique. Several strains of bacteria caused release of histamine from peripheral leukocytes in vitro. Normal, non-infectious and non-atopic children frequently responded in a similar fashion, although positive responses were less frequent. It seems that two different mechanisms of bacterial histamine release exist: interaction with the basophil-bound IgE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It has previously been shown that bacteria can induce histamine release from human basophil leukocytes in vitro in both normal individuals and patients with intrinsic asthma (10,18,19), and a similar release was observed in human lung mast cells (2). In this study we examined the effect of influenza A virus on histamine release caused by S. aureus.…”
Section: Discussionmentioning
confidence: 88%
“…It has previously been shown that bacteria can induce histamine release from human basophil leukocytes in vitro in both normal individuals and patients with intrinsic asthma (10,18,19), and a similar release was observed in human lung mast cells (2). In this study we examined the effect of influenza A virus on histamine release caused by S. aureus.…”
Section: Discussionmentioning
confidence: 88%
“…It seems that at least two different mechanisms are involved in this bacterial histamine release: an immunoglobulin E (IgE)-dependent mechanism, in which removal of IgE from the basophils abolished or reduced the bacteria-induced histamine release, and a nonimmunological mechanism, in which this was not the case (6). We found that bacterial ultrasonicates of several strains from the normal flora of the upper respiratory tract caused release of histamine from basophil leukocytes in both intrinsic asthma patients and normal individuals (8,13). This release might be a pathogenic mechanism in intrinsic asthma and in bacterial infections.…”
mentioning
confidence: 87%
“…through interaction with the specific receptors on the surface of mast cells, induce a slow release of chemical mediators [58]. In addition, components of bacterial cell walls may directly interact with the surface of mast cells and basophils, to initiate mediator secretion by a non-immunological mechanism [59]. Thus, it is possible that within the airways selective bacteria may incite mast cell mediator release with the inflammatory consequences that this may produce.…”
Section: Non-specific Mechanismsmentioning
confidence: 99%